Suluk “Sigra Bala Kang Tumingal”: Sumber Inspirasi Nilai Kehidupan Dalam Meningkatkan Pendidikan Karakter Bagi Siswa SMPN 3 Grogol - Rista , Diana; Hanggara, Guruh Sukma; Sasmita, Wikan (Philosophiamundi, 2024)
SMPN 3 Grogol, known as Simpatig Budaya, is a school rich in cultural diversity and committed to preserving local cultural heritage, including wayang art. This research focuses on the suluk "Sigra Bala Kang Tumingal," one of Sinom's macapat songs used in wayang performances to add depth to the story and depict the spirit and courage of the troops. This suluk functions as entertainment and a medium for conveying moral values and philosophy of life. By integrating these suluk values into the character of education at SMPN 3 Grogol, it is hoped that it can form students who have integrity, responsibility and an attitude of respect for differences, as well as empowering them as active cultural actors in preserving the nation's cultural heritage.